Public awareness of paper’s sustainability in a digital society - Hye Jung Youn; Hak Lae Lee (BioResources)
People often think of paper as an environmentally harmful product because trees are cut down to make it. A new generation that has grown up in today’s digital society may think that the use of digital devices is a waste-free way to protect our environment. Although the pulp and paper industry is making various efforts to preserve the environment, it has not been properly recognized. Developing new technologies to produce better products at lower cost while protecting our environment is important. But it is also important to enhance the image of the pulp and paper industry in the eyes of the public. The pulp and paper industry’s efforts to reforestation for raw materials and to expand the recycling of waste paper should be more widely introduced.